Impaired neutrophil function in intestinal lymphangiectasia. Issue 8 (August 1986) - Bolton, R P; Cotter, K L; Losowsky, M S
Abstract : Impaired neutrophil chemotaxis and phagocytosis were shown in three patients with intestinal lymphangiectasia. Abnormalities in cell associated and serum derived activity occurred, and possible mechanisms are suggested.